2002
DOI: 10.1128/aem.68.5.2246-2250.2002
|View full text |Cite
|
Sign up to set email alerts
|

Linking Central Metabolism with Increased Pathway Flux: l -Valine Accumulation by Corynebacterium glutamicum

Abstract: Mutants of Corynebacterium glutamicum were made and enzymatically characterized to clone ilvD and ilvE, which encode dihydroxy acid dehydratase and transaminase B, respectively. These genes of the branched-chain amino acid synthesis were overexpressed together with ilvBN (which encodes acetohydroxy acid synthase) and ilvC (which encodes isomeroreductase) in the wild type, which does not excrete L-valine, to result in an accumulation of this amino acid to a concentration of 42 mM. Since L-valine originates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
104
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 41 publications
6
104
0
Order By: Relevance
“…Still, glucose feeding, aeration, pH, and the medium components appeared to play important roles in controlling the yield of valine. Further genetic engineering involving ilvA knockout, ilvD introduction, and panBC knockouts seem to be useful for more efficient valine production, as reported previously 27,28) and might be applicable in combination with our results (Fig. 1).…”
Section: Discussionsupporting
confidence: 65%
“…Still, glucose feeding, aeration, pH, and the medium components appeared to play important roles in controlling the yield of valine. Further genetic engineering involving ilvA knockout, ilvD introduction, and panBC knockouts seem to be useful for more efficient valine production, as reported previously 27,28) and might be applicable in combination with our results (Fig. 1).…”
Section: Discussionsupporting
confidence: 65%
“…There have only been a few reports of attempts to engineer increased valine content in bacteria. These studies in bacteria either increased the pathway flux to valine (Radmacher et al, 2002;Blombach et al, 2007), utilized mutated valine-tolerant RSUs to circumvent end-product inhibition (Elisakova et al, 2005), or combined both strategies (Park et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Functionally identified ATs of this organism include the N-succinyl-2,6-diaminopimelate AT (dapC) involved in the synthesis of L-lysine, of which 650,000 tonnes per year (t/y) are produced with C. glutamicum (5), as well as ilvE, encoding the branched-chain AT necessary for L-isoleucine production (26). Mutant studies further identified the genes (and respective enzymes) bioA (adenosylmethionine-8-amino-7-oxononanoate aminotransferase) (10), argD (N-acetyl-ornithine AT) (29), and pat and pdxR (involved in aromatic amino acid and pyridoxal-5Ј-phosphate synthesis, respectively) (19).…”
mentioning
confidence: 99%